Imaging and diffraction characterisation of 2D inorganic nanostructures - Shmeliov, A; Shannon, M; Wang, P; E, H; Nellist, P; Nicolosil, V (2012)
2D nanomaterials are a novel class of materials, noted for their potential in a range of high impact applications, such as sensing catalysis, and composite reinforcement. However, their structural features have not yet been fully characterised. In this work we have shown that 2D nanostructures of hBN, MoS 2, and WS 2, prepared by liquid exfoliation, can stack in sequences different from the bulk stacking. In 2D hBN non-sequential stacking was observed. 2D MoS 2 and WS 2 appear to have stacking where Mo/W atoms are located on the top of each other which differs from naturally occurring 2H and 3R polytypes. The majority of the hBN and MoS 2 2D nanostructures retain the stacking of their bulk counterparts, while in 2D WS 2 non-bulk stacking dominates. The conclusions are based primarily on the atomically resolved ADF STEM images with supporting evidence from electron diffraction.